2013
DOI: 10.1016/j.msea.2013.06.070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of twinning and detwinning on inelastic behavior during unloading in a magnesium alloy sheet

Abstract: We investigate the nonlinear response arising during unloading under in-plane uniaxial compression of a rolled magnesium alloy sheet using a crystal plasticity finite-element method, focusing on the effects of twinning and detwinning, and discuss the mechanism that causes the nonlinear response to be more pronounced under uniaxial compression than under uniaxial tension. In the simulation, we employed a twinning and detwinning model recently proposed by the authors. From numerical experiments, we confirmed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 64 publications
2
39
0
Order By: Relevance
“…A twinning and detwinning [11][12][13] mechanism cannot explain experimentally observed nonlinearity in non-HCP structured metals.…”
Section: Discussionmentioning
confidence: 99%
“…A twinning and detwinning [11][12][13] mechanism cannot explain experimentally observed nonlinearity in non-HCP structured metals.…”
Section: Discussionmentioning
confidence: 99%
“…Because a crystal plasticity analysis on unloading processes has scarcely been conducted except for our previous works in a Mg alloy sheet, 24,25) the availability of a crystal plasticity analysis on unloading processes in various materials are not understood yet. Therefore, in the present study, the applicability of a crystal plasticity analysis on unloading processes is also discussed.…”
Section: Crystal Plasticity Finite-element Methodsmentioning
confidence: 99%
“…We also depicted that the nonlinear deformation during unloading in the Mg alloy sheet can be predicted well using a crystal plasticity finiteelement simulation. 24,25) The aforementioned studies exhibited that the nonlinear deformation during unloading is observed in various metal sheets and the nonlinearity during unloading plays an important role in the springback prediction. Recently the nonlinear effects are being taken into account in the constitutive models.…”
Section: Introductionmentioning
confidence: 99%
“…The stress-strain curves of Mg alloy sheets are significantly different between tension and compression [21,31,[40][41][42]. Moreover, a sigmoidal curve occurs when a Mg alloy sheet is subjected to compression followed by tension, whereas this curve does not occur under tension followed by compression [20,21,41].…”
Section: Effect Of Twinning Activity On Mechanical Behaviormentioning
confidence: 99%
“…The abovementioned asymmetric work-hardening behaviors arise because of the activities of <101 � 2> twinning and detwinning [20,[40][41][42]. Clearly, the twinning activity plays an important role in the stressstrain curves in Mg alloy sheets.…”
Section: Effect Of Twinning Activity On Mechanical Behaviormentioning
confidence: 99%